Answer:
7 sales
Step-by-step explanation:
Answer: 6.3
Step-by-step explanation:
The formula for geometric mean is given as :
G.m = ![\sqrt{pq}](https://tex.z-dn.net/?f=%5Csqrt%7Bpq%7D)
Therefore , the geometric mean between 4 and 10 will be :
G.m = ![\sqrt{4(10)}](https://tex.z-dn.net/?f=%5Csqrt%7B4%2810%29%7D)
= ![\sqrt{40}](https://tex.z-dn.net/?f=%5Csqrt%7B40%7D)
= 2![\sqrt{10}](https://tex.z-dn.net/?f=%5Csqrt%7B10%7D)
= 6.3
Answer:
![\frac{4x+2}{x^2 - 9x + 8} = \frac{4x}{(x-8)(x-1)} + \frac{2}{(x-8)(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%2B2%7D%7Bx%5E2%20-%209x%20%2B%208%7D%20%3D%20%5Cfrac%7B4x%7D%7B%28x-8%29%28x-1%29%7D%20%2B%20%5Cfrac%7B2%7D%7B%28x-8%29%28x-1%29%7D)
Step-by-step explanation:
Given
![\frac{4x+2}{x^{2}-9+8 } = \frac{A}{()(x-1)} + \frac{B}{()(x-8)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%2B2%7D%7Bx%5E%7B2%7D-9%2B8%20%7D%20%3D%20%5Cfrac%7BA%7D%7B%28%29%28x-1%29%7D%20%2B%20%5Cfrac%7BB%7D%7B%28%29%28x-8%29%7D)
Required
Fill in the gaps
Going by the given parameters, we have that
![\frac{4x+2}{x^{2}-9+8 } = \frac{A}{()(x-1)} + \frac{B}{()(x-8)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%2B2%7D%7Bx%5E%7B2%7D-9%2B8%20%7D%20%3D%20%5Cfrac%7BA%7D%7B%28%29%28x-1%29%7D%20%2B%20%5Cfrac%7BB%7D%7B%28%29%28x-8%29%7D)
, when factorized is ![(x-1)(x-8)](https://tex.z-dn.net/?f=%28x-1%29%28x-8%29)
Hence; the expression becomes
![\frac{4x+2}{(x-1)(x-8)} = \frac{A}{(x-8)(x-1)} + \frac{B}{(x-1)(x-8)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%2B2%7D%7B%28x-1%29%28x-8%29%7D%20%3D%20%5Cfrac%7BA%7D%7B%28x-8%29%28x-1%29%7D%20%2B%20%5Cfrac%7BB%7D%7B%28x-1%29%28x-8%29%7D)
Combine Fractions
![\frac{4x+2}{(x-1)(x-8)} = \frac{A + B}{(x-8)(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%2B2%7D%7B%28x-1%29%28x-8%29%7D%20%3D%20%5Cfrac%7BA%20%2B%20B%7D%7B%28x-8%29%28x-1%29%7D)
Simplify the denominators
![4x + 2 = A + B](https://tex.z-dn.net/?f=4x%20%2B%202%20%3D%20A%20%2B%20B)
By direct comparison
![A = 4x](https://tex.z-dn.net/?f=A%20%3D%204x)
![B = 2](https://tex.z-dn.net/?f=B%20%3D%202)
Hence, the complete expression is
![\frac{4x+2}{x^2 - 9x + 8} = \frac{4x}{(x-8)(x-1)} + \frac{2}{(x-8)(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B4x%2B2%7D%7Bx%5E2%20-%209x%20%2B%208%7D%20%3D%20%5Cfrac%7B4x%7D%7B%28x-8%29%28x-1%29%7D%20%2B%20%5Cfrac%7B2%7D%7B%28x-8%29%28x-1%29%7D)
Answer:
The expressions for the payment made to Mary are,
(Monday) 90 = 15m + b
(Tuesday) 62 = 8m + b
where m and b are the fee per student and the base fee, respectively. Solving for m and b, the values are 4 and 30.
The equation that represents Mary's earning is
y = 4x + 30
For 20 students,
y = 4(20) + 30 = 110
For Lisa's earnings,
y = 8x + 15
Substituting 20,
y =8(20) + 15 = 175
Thus, Lisa would earn more than Mary by $65.
(Btw this is not my work, I got it from someone else on brainly and wanted to help lol)